Hearing Threshold of Auditory Brainstem Response in Term Neonates with Hyperbilirubinemia - Fatemeh Eghbalian; Farhad Farahani; Amirreza Monsef Esfehani; Ehsan Mazloumi; Manoochehr Karami; Mohammad Jafari (Journal of Kerman University of Medical Sciences, 2021)
Background:Neonatal jaundice is a common cause of premature neonatal hearing loss and is a major cause of childhood deafness, especially in developing countries. The aim of this study was evaluating Hearing threshold of Auditory Brainstem Response (ABR) in term neonates admitted with hyperbilirubinemia at a range of exchange transfusion and near exchange transfusion. Methods: This cross-sectional study was performed on 134 healthy term infants admitted due to hyperbilirubinemia in the neonatal care unit of Besat Hospital in Hamadan from March 2017 to September 2017. All neonates were evaluated by Otoacoustic Emission (OAE) and ABR after admission in neonatal ward and after treatment by intensive phototherapy or blood              exchange. Data were collected and analyzed through SPSS software and using Chi-square and Mann-Whitney tests. The significance level was considered at 0.05 for all statistical tests. Results: The mean weight of newborns was 3000 ±350 gr and the mean of gestational age was 39± 2 weeks. Bilirubin concentration of the infants was 36.9±9.2 mg/dL. There was a significant difference between hearing loss on auditory brainstem response in term neonates according to hyperbilirubinemia in blood exchange range (P = 0.001). However, there was no significant difference between hearing loss on auditory brainstem response in term neonates according to the gestational age, sex and phototherapy (P > 0.05). Conclusion: Our findings indicated that high bilirubin levels in the range of exchange transfusion can be an important risk to the auditory system, which without creating kernicterus, can interfere with auditory tests.